Ekonomi Publik pada Analisis Dampak Program Perlindungan Sosial Terhadap Penurunan Angka Kemiskinan di Perkotaan - Ahmad Wahyudi Zein; Syifwa Nurdilla Gusvi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative literature review method to analyze the impact of social protection programs on poverty reduction in urban areas from a public economics perspective. The main focus of this research is to evaluate the effectiveness of various government social interventions such as cash assistance, basic needs subsidies, and social security, based on scholarly literature, journals, and official policy documents. Social protection programs are considered vital instruments in improving the welfare of poor and vulnerable populations, especially in urban environments with complex socio-economic dynamics. The findings show that well-planned and well-targeted social protection plays a significant role in reducing household expenditures among the poor, increasing purchasing power, and strengthening economic resilience. In addition, social protection can encourage economic participation among vulnerable groups through empowerment and improved access to basic services. This study also highlights the importance of institutional synergy and continuous evaluation to ensure that social protection policies have a long-term impact on poverty alleviation.